2019
DOI: 10.1097/md.0000000000015729
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of back pain and the knowledge of preventive measures in a cohort of 11619 Polish school-age children and youth—an epidemiological study

Abstract: The study sought to characterize back pain (BP) (in the period of 12 months) in children and youth aged 10 to 19 from eastern Poland. The study included 11619 children and youth (6254 girls and 5365 boys) aged 10 to 19 from eastern Poland. An original questionnaire was applied as a research tool. Before the study, the reliability of the questionnaire had been assessed. The Kappa coefficient value for all the analyzed variables was equal to or higher than 0.91. Over 74.4% of the respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…Als alternativer Kompensationsmechanismus gilt der Rundrücken, wobei das Becken aufgerichtet und die Lendenlordose aufgehoben wird und bei vorgeschobenem Kopf ein nach vorne gewölbter thorakaler Rundrücken entsteht. Für beide Mechanismen, die Hohlkreuzhaltung als auch der thorakale Rundrücken, sollte eine Stärkung der Rückenmuskulatur als Präventionsmaßnahme gegen Rückenschmerzen diskutiert werden [ 19 ]. Auch das Design des Schulrucksacks in Bezug auf Ergonomie und Passgenauigkeit an der Rückenpartie sowie die Tragegewohnheiten, insbesondere die symmetrische Verteilung der Last auf beide Schultern, spielen eine Rolle [ 2 , 26 ].…”
Section: Diskussionunclassified
“…Als alternativer Kompensationsmechanismus gilt der Rundrücken, wobei das Becken aufgerichtet und die Lendenlordose aufgehoben wird und bei vorgeschobenem Kopf ein nach vorne gewölbter thorakaler Rundrücken entsteht. Für beide Mechanismen, die Hohlkreuzhaltung als auch der thorakale Rundrücken, sollte eine Stärkung der Rückenmuskulatur als Präventionsmaßnahme gegen Rückenschmerzen diskutiert werden [ 19 ]. Auch das Design des Schulrucksacks in Bezug auf Ergonomie und Passgenauigkeit an der Rückenpartie sowie die Tragegewohnheiten, insbesondere die symmetrische Verteilung der Last auf beide Schultern, spielen eine Rolle [ 2 , 26 ].…”
Section: Diskussionunclassified
“…Epidemiological data have shown that low back pain (LBP) is not only a health problem for adults but is also frequently reported by schoolchildren [1][2][3][4][5][6][7][8][9][10][11][12]. The prevalence of LBP in children and adolescents increases with subjects' age [13][14][15], and females demonstrate its higher occurrence [2,7,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of LBP in children and adolescents increases with subjects' age [13][14][15], and females demonstrate its higher occurrence [2,7,16,17]. A recent study found that the self-reported prevalence of LBP was 31%, 51.9% and 71.2% among children aged 10-13, 14-16 and 17-19 years, respectively [11]. Back pain during this period of life may have health implications in adulthood [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of the questionnaire was assessed. The Kappa coefficient value for all the analysed variables was equal to or higher than 0.91 ( Kędra et al, 2019 ).…”
Section: Methodsmentioning
confidence: 84%
“…A questionnaire was applied as a research tool ( File S2 ) ( Kędra et al, 2019 ). The questionnaire was completed in the presence of one of the authors of the paper.…”
Section: Methodsmentioning
confidence: 99%